Investigation on the Effects of Different Coil Spring Materials on Vehicle Ride Comfort and Handling - Partheeban, Nadaraj; Ibrahim, Mohd Norihan (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This research investigates the effects of different coil spring materials on vehicle ride comfort and handling. Utilizing ANSYS simulation software, we analyzed the performance and fatigue behavior of automotive springs made from Monel 400, MP35N, and A286. The study aims to understand how these materials impact the operational efficacy and durability of suspension systems. The results indicate significant variations in performance metrics, with Monel 400 showing potential for superior ride comfort due to its high strength and corrosion resistance, MP35N demonstrating excellent fatigue resistance and strength-to-weight ratio, and A286 providing hightemperature stability. These findings contribute valuable insights for optimizing material selection in automotive spring design, enhancing both vehicle performance and ride quality.